BDNF Induced Translation of Limk1 in Developing Neurons Regulates Dendrite Growth by Fine-Tuning Cofilin1 Activity - Ravindran, Sreenath; Nalavadi, Vijayalaxmi C.; Muddashetty, Ravi S. (Frontiers in Molecular Neuroscience, 2019)
Dendritic growth and branching are highly regulated processes and are essential for establishing proper neuronal connectivity. There is a critical phase of early dendrite development when these are heavily regulated by external cues such as trophic factors. Brain-Derived Neurotrophic Factor (BDNF) is a major trophic factor known to enhance dendrite growth in cortical neurons, but the molecular underpinnings of this response are not completely understood. We have identified that BDNF induced translational regulation is an important mechanism governing dendrite development in cultured rat cortical neurons. We show that BDNF treatment for 1hour in young neurons leads to translational up-regulation of an important actin regulatory protein Limk1, increasing its level locally in the dendrites. Limk1 is a member of Ser/Thr family kinases downstream of the Rho-GTPase pathway. BDNF induced increase in Limk1 levels leads to increased phosphorylation of its target protein cofilin1. We observed that these changes are maintained for long durations of up to 48 hours and are mediating increase in number of primary dendrites and total dendrite length. Thus we show that BDNF induced protein synthesis leads to fine-tuning of the actin cytoskeletal reassembly and thereby mediate dendrite development.